Trends and patterns of Greek outward FDI in CEE countries - Dimitris Giakoulas (International Journal of Business and Economic Sciences Applied Research (IJBESAR), 2021)
Purpose: This paper focuses on the internationalization of the Greek Multinational Enterprises in Central and Eastern European Countries. Its purpose is twofold. Firstly, to describe the process through which Greece became a major investor in the region following the collapse of the central planned economies. Secondly, to investigate if there are any different patterns between firms investing in Central and Eastern European Countries and those investing in other EU countries. Design/methodology/approach: Using firm level data and a descriptive qualitative approach we analyse the investment trends in the two regions and find indications of different patterns in the volumes and sectoral allocation of FDI. Findings: A major finding of this study is that Greek FDI in Central and Eastern European Countries follow different patterns in terms of volume, sector and industrial activity, compared to the respective FDI in other EU countries Research limitations/implications: The firm level data used in this study refer to the specific year that each FDI was announced; In this respect one major limitation is that we cannot trace any increase of invested capital or disinvestment to subsidiaries which are already established. Originality/value: This paper contributes significantly to the existing literature since it is one of the few studies examining the total of a country's outward FDI in the CEE Countries at sectoral level, using firm lever data in an extended time series extending both in pre-crisis and postcrisis periods.
Keywords: F23; 330; FDI; Multinational Enterprises; CEEC; internationalization; Greece; debt crisis